The Impact of Service Quality Dimensions on Visitors’ Satisfaction towards the Theme Parks of Bangladesh: An Empirical Study on Fantasy Kingdom Based on SERVQUAL Model - Bappy, Tauhid Ahmed; Halim, Samiya Bint (AIUB Journal of Business and Economics, 2018)
The purpose of this study was to measure the impact of service quality dimensions on visitors’ satisfaction towards theme parks of Bangladesh. This was a descriptive research and the researchers took visitors from Fantasy Kingdom theme park as sample. In this study, the researchers used stratified sampling technique and the sample size used for final data analysis turned out to be 150 park visitors. The researchers used factor analysis and multiple regression analysis to analyse the data. Firstly, through factor analysis, multiple items measuring service quality were reduced into five factors such as reliability, assurance, tangibles, empathy, and responsiveness. Then, regression analysis was conducted to investigate the relative importance of the factors responsible for influencing visitors’ satisfaction. However, the researchers found that all the identified factors significantly and positively contributed to visitors’ satisfaction and tangible elements of theme park turned out to be the most crucial factor in this regard. The researchers believe that the findings and recommendations presented in this study may be followed by the managers of theme parks in Bangladesh to improve their service quality to achieve visitors’ satisfaction.